2003
DOI: 10.1016/s0304-3959(02)00327-5
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in postoperative pain are scale dependent: a comparison of measures of pain intensity and quality in younger and older surgical patients

Abstract: As the population ages, research into the assessment of postoperative pain in older patients is urgently needed. The reliability and validity of most pain scales for the assessment of acute postoperative pain in the elderly remain to be demonstrated. The present study reports the analysis of age-related patterns on three pain scales (McGill Pain Questionnaire, MPQ; Present Pain Intensity, PPI; and Visual Analog Scale, VAS) completed by younger (n:95, mean age:56.4r-5.8 years) and older (n:105; mean age:66.8 +2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
109
1
9

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(125 citation statements)
references
References 43 publications
6
109
1
9
Order By: Relevance
“…However, the present findings are also contrary to the previous study (Gagliese & Katz, 2003) reporting that age differences in the convergent validity were evident since the correlation between the VAS and the McGill Pain Questionnaire (MPQ) scores was significantly lower in the old adult group than young adult group. This discrepancy might be explained by the methodological differences in evaluating convergent validity between Gagliese and Katz's study and the present study.…”
Section: Convergent Validity Of the Pain Intensity Scalescontrasting
confidence: 99%
See 2 more Smart Citations
“…However, the present findings are also contrary to the previous study (Gagliese & Katz, 2003) reporting that age differences in the convergent validity were evident since the correlation between the VAS and the McGill Pain Questionnaire (MPQ) scores was significantly lower in the old adult group than young adult group. This discrepancy might be explained by the methodological differences in evaluating convergent validity between Gagliese and Katz's study and the present study.…”
Section: Convergent Validity Of the Pain Intensity Scalescontrasting
confidence: 99%
“…For one thing, the findings of age differences in the psychometric properties of the pain scales are inconsistent. Some studies found that age differences in the psychometric properties of the pain scales were evident (Gagliese & Katz, 2003;Peters et al, 2007). However, another study failed to find the age differences in the psychometric properties of the pain scales (Li et al, 2007).…”
Section: Theoretical Framework Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Older patients, matched for surgical procedure, reported less pain in the postoperative period: pain intensity decreased by 10% to 20% each decade after 60 years of age Level III-2). Older men undergoing prostatectomy reported less pain on a present pain intensity scale and McGill Pain Questionnaire (but not a visual analogue scale [VAS]) in the immediate postoperative period and used less PCA opioid than younger men undergoing the same procedure (Gagliese & Katz, 2003 Level III-2). In a study of pain following placement of an IV cannula (a relatively standardised pain stimulus), older patients reported significantly less pain than younger patients (Li et al, 2001 Level IV).…”
Section: Discussionmentioning
confidence: 99%
“…In some practice settings, the experiences of older and younger people have been compared to examine pain and analgesic administration and all of the research found no difference in pain intensity between the groups. However, analgesic consumption has been significantly lower in older age groups (Oberle et al 1990, Feldt et al 1998, Celia 2000, Gagliese et al 2000, Gagliese & Katz 2003. Health care professionals administering more analgesics to younger people, older people under-reporting pain and increased sensitivity to opioid analgesia in older people have all been offered as explanations.…”
mentioning
confidence: 99%